2020
DOI: 10.1016/j.npbr.2020.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Mental health research in the lower-middle-income countries of Africa and Asia during the COVID-19 pandemic: A scoping review

Abstract: Highlights There is a paucity of COVID-19 related mental health publications in lower middle-income countries. Existing research in mental health are mostly online community survey to measure different domains of psychopathology in the context of COVID-19. There is gross scarcity of original high quality research in Afro-Asian LMIC countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 64 publications
(78 reference statements)
1
30
0
Order By: Relevance
“…These aspects are highly prominent in low- and middle income countries which might further increase the risk for mental health problems. A recent review on the impact of the COVID-19 pandemic on mental health in low- and middle income countries across Asia and Africa [ 29 ] points out that most studies investigating this topic report increased levels of depression, post-traumatic stress disorder, adjustment disorders, addiction problems, sleep disorders, and anxiety disorders; the lack of thorough investigation of mental health in general and the poor quality of infrastructure for prevention and intervention remain pressing problems in low- and middle income countries.…”
Section: Discussionmentioning
confidence: 99%
“…These aspects are highly prominent in low- and middle income countries which might further increase the risk for mental health problems. A recent review on the impact of the COVID-19 pandemic on mental health in low- and middle income countries across Asia and Africa [ 29 ] points out that most studies investigating this topic report increased levels of depression, post-traumatic stress disorder, adjustment disorders, addiction problems, sleep disorders, and anxiety disorders; the lack of thorough investigation of mental health in general and the poor quality of infrastructure for prevention and intervention remain pressing problems in low- and middle income countries.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, having up-to-date and accurate health information and taking precautionary measures have been found to be protective against stress, anxiety, and depression [ 21 ]. However, factors associated with psychological distress in Southern Africa during the ongoing pandemic have not been widely investigated [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a review assessing the prevalence of depression among universities students in low and middle income countries (LMICs) and that included three studies in Africa, found a depression prevalence of 34.2% for African students [36]. On another side, while focusing on the COVID-19 pandemic mental health impact amid the general population in Africa during this pandemic, there is a scarcity of review articles [37]. Nevertheless, a systematic review of the prevalence of anxiety among the general population during the COVID-19 pandemic found that the prevalence in Africa was 61.8% (95% CI, 57%-66.4%) [38], which is higher than the one we found.…”
Section: General Interpretation Of the Results In The Context Of Other Evidencementioning
confidence: 99%